The Influence of Work-Life Balance and Non-Physical Work Environment on Employee Job Satisfaction in a Digital Consulting Company - Akbar , Wahyu; Afriyani, Fauziah; Kurniawan DP, Mohammad (JEM17: Jurnal Ekonomi Manajemen, 2025)
This study analyzes the effect of work-life balance and non-physical work environment on employee job satisfaction at PT Brilliant Think Center. The research is motivated by the imbalance between employees’ work and personal lives, as well as a non-physical work environment that has not been fully optimized. This study employs a quantitative approach with descriptive and associative methods. The population consists of 125 employees, and 95 respondents were selected using the Slovin formula. Primary data were collected through questionnaires and analyzed using multiple linear regression, t-test, and F-test. The results show that work-life balance and the non-physical work environment have a positive and significant effect on job satisfaction, with an R Square value of 0.676, indicating that both variables explain 67.6% of the variation in job satisfaction. These findings highlight the practical importance of improving work flexibility, strengthening internal communication, and fostering a supportive workplace atmosphere to enhance employee job satisfaction and retention. Keywords: Work-Life Balance, Non-Physical Work Environment, Job Satisfaction.